R-R interval variation and sympathetic skin response in systemic lupus erythematosus - Tekatas, Aslan; Koca, Suleyman Serdar; Tekatas, Demet Deniz; Aksu, Feyza; Dogru, Yuce; Pamuk, Omer Nuri (Springer London Ltd, 2014)
The involvement of the autonomic nervous system is less common than that of the central and peripheral nervous system in systemic lupus erythematosus (SLE) patients. However, its involvement can negatively affect the quality of life of the patient and cause life-threatening situations. In this study, autonomic function was evaluated in SLE patients who did not show any sign of autonomic involvement using R-R interval variation (RRIV) and sympathetic skin response (SSR) electrophysiological tests. SSR was used to evaluate the sympathetic nervous system, whereas RRIV was used for the parasympathetic nervous system. We included 23 SLE patients and 21 healthy volunteers in the study. Of the 23 SLE patients, 20 (86.9 %) were female and 3 (13.1 %) were male. The age range of the patients was between 19 and 52 years, with a mean age of 32.5 +/- 9.1 years. Routine nerve conduction studies and autonomic tests were performed on patients in the electromyography (EMG) laboratory. Lower extremity SSR latencies were prolonged and a significant loss of amplitude was observed in comparison to the control group. Furthermore, deep-breath RRIV values for the patient group were significantly lower than that of the control group. Both sympathetic and parasympathetic nervous system involvement was seen in our study. In conclusion, EMG can reveal a possible underlying involvement in the absence of signs of autonomic involvement.
Keywords: Autonomic dysfunction; Electromyography; R-R interval variation; Sympathetic skin response; Systemic lupus erythematosus